Paradigma Tanggung Jawab Hukum Pemerintah Dan Korporasi Terhadap Korban Bencana - Suharto (Jurnal Hukum Dan Keadilan, 2010)
paradigm of the enforcement of the environment law has not been well implemented. It can be observed through the incapability of the government to stop some actions damaging the environment done by some corporations. On the other hand, based on the principles of the environment law it is stated that the government is the one who is liability for the management of the environment. The topic of the study is essential to disclose the background whether or not there are some violations towards theregulations done by Corporation. The result of the study indicated that the paradigm of the enforcement of the environment law stated in UU No. 32 the year 2009 on the protection and the management of environment, UU No. 24 the year 2007 on the Protection on Disaster, UU No. 30 the year 1999 on AAPS (Arbitration and Alternative for Dispute Settlement) and UU No. 4 the year 2009 on mining were still in the form of normative paradigm leading to the weakness of the enforcement of evironmet law.